Intraoperative Auditory Brainstem Response Results Predict Delayed Sensorineural Hearing Loss After Middle Cranial Fossa Resection of Vestibular Schwannoma. Issue 6 (July 2021) - Welch, Christopher M.; Mannarelli, Gregory; Koehler, Lindsey; Telian, Steven A.
Abstract : Objective: To identify intraoperative neurophysiologic measures predictive of delayed progressive sensorineural hearing loss in the operative ear after a middle fossa approach (MCF) for resection of vestibular schwannoma (VS). Study Design: Retrospective review. Setting: Academic, tertiary referral center. Patients: Subjects with vestibular schwannoma who underwent a MCF microsurgical resection of VS were analyzed for individuals whose hearing was initially preserved but subsequently developed progressive sensorineural hearing loss in the operative ear. Thirty-seven patients were identified for whom audiologic and neurophysiologic data was available. Intervention: Intraoperative neurophysiologic changes will correlate with delayed sensorineural hearing loss in the operative ear. Main Outcome Measures: Audiometric evaluations, intraoperative electrocochleography (ECoG), and auditory brainstem response (ABR) measures. Results: Twenty-five subjects experienced stable hearing or hearing loss in the operative ear comparable to the contralateral ear. Twelve subjects suffered a significant increase in the hearing asymmetry between ears. Deterioration in the amplitude of wave V of the ABR persisting at the close of tumor resection correlated with delayed sensorineural hearing loss in the operative ear ( p 0.02, 5% mean improvement in the stable hearing group, versus a 14% decline with progressive asymmetry), but changes in ECoG or other auditory brainstem response parameters ( p > 0.05) were not predictive. Conclusions: Persisting amplitude reduction of wave V of the intraoperative ABR best correlates with delayed progressive sensorineural hearing loss in the operative ear. Neither persistent changes in ECoG, other ABR parameters, nor transient changes, correlated with delayed progressive sensorineural hearing loss in the operative ear.